Exploring Teacher Burnout: A Comprehensive Study of Causes and Solutions - Joshi, Rajendra Prasad (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
Teacher burnout is a growing concern in the education field, significantly impacting educators’ well-being, job satisfaction, and students' performance. This study explores the causes of teacher burnout in Nepalese schools and proposes practical solutions to mitigate its effects. Using a narrative inquiry approach, the research gathered detailed qualitative data from four school teachers and two teacher educators through a random sampling method. The results showed that excessive workload, lack of administrative support, financial stress, students' behavioral problems, and socio-cultural expectations are significant factors contributing to burnout. Teachers reported that emotional exhaustion lowers motivation and raises absenteeism, which negatively affects classroom effectiveness. The study also emphasizes the negative correlation between teachers' burnout and students' academic success, underscoring the need for targeted interventions. Suggested solutions include managing workload effectively, implementing professional development programs, offering mindfulness training, promoting wellness initiatives, and fostering a supportive work environment. The research highlights the significance of institutional and policy-level changes in enhancing teacher well-being and, consequently, improving educational quality. This work contributes to the limited research on teacher burnout in Nepal and provides practical recommendations for educators, administrators, and policymakers to foster a more sustainable and motivating teaching career.